'Phaser' metal detector / Baharam Yahaya and Mohamad Saad - Yahaya, Baharam; Saad, Mohamad (1989)
This report explained the purpose of PHASER METAL DETECTOR, how it works and some of its application, taking for granted that the reader has acquired some basic knowledge in electrical and electronics circuit theory'. The report has been made chapter by chapter by introducing the principles and the buildings blocks which make up a phaser metal detector. The chapters include the actual construction of the phaser metal detector, some theory of the components used and the operation. Also included are discussion and the numerous illustrations which will help to reinforce the text.